Study on the impact of the promotions towards customer acceptance the Mayban financial hire purchase: case study analysis in MBF Mentakab Pahang / Mimi Zelia Mustapa - Mustapa, Mimi Zelia (Faculty of Business and Management, 2002)
Finance companies were a phenomenon of the 1960's as limited companies engaged with many lending activities. Therefore Mayban Finance Berhad as one of Maybank Group subsidiaries leading the other finance companies as the largest bank - backed finance companies in Malaysia by providing quality finance services This researches focus on the impact of the Mayban Finance Hire Purchase promotions and advertisement towards the customer acceptance. Promtions involve the tools and the media used by Mayban Finance Mentakab in order to attract customer awareness as well as their acceptance. This involves pamphlet, posters, advertisement in newspapers, Internet and others promotional tools implemented by Mayban Finance.